(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Chasova E. V., Ivchuk V. V. Topical issues of the initial course of teaching chemistry to foreign engineering students at the preparatory department of the University. The main problems of teaching foreign students in foreign universities. Identified several factors that influence the success of the educational process. Shows a function effectively adapted training and methodological support, which aims to intensify the process of learning the basics of chemistry. Consider the key role of teachers in shaping the student’s ability to psychological self-government and as a carrier of information.